The perceived demands of Rugby Sevens held by professional players and coaching staff - Kruyt, N. (Stellenbosch University, 2017)
There appears to be a lack of psychological support in rugby sevens, including the absence of psychological skills development programmes and research on this topic. This study aimed to address the glaring gap in this field by laying a foundation for the development of an effective programme to equip players with psychological skills to enhance their performance and psychological well-being. The potential outcome will be advantageous both for individual players and the sport as a whole. The thesis set out to explore the subjective views of professional players and coaching staff regarding the demands of rugby sevens. A thorough analysis of the physical, technical and tactical, logistical and psychological demands, as well as the specific needs of the players was deemed necessary. According to Taylor (1995) it is essential to establish these demands in order to develop a psychological skills development programme for a specific sport or athlete. The primary aim of this study was, therefore, to analyse the perceived demands of rugby sevens held by professional players and coaching staff. Twenty-five participants (20 rugby sevens players and five coaching staff members) took part in the study. The 20 players consisted of three sub-groups: SA academy players (n=3), Blitzboks (n=8) and Olympians (n=9). Information was mainly elicited through semi-structured interviews. The coaching staff members were asked 21 open-ended questions while the players were asked 25 open-ended questions. The data was analysed through a thematic content analysis. This analysis revealed numerous challenges with regards to the physical, technical and tactical and logistical demands of rugby sevens. Due to the setup of the tournaments and matches, the demands of rugby sevens are different to that of other rugby formats. Therefore, a different approach needs to be taken when preparing players for tournaments. Being exposed to such a demanding sport also places considerable psychological demands on the players. A strong team culture was reported as one of the South African sevens team`s strengths and seemingly played a fundamental part in the team`s success. However, there seems to be an insufficient focus on the psychological side of the sport. The need to start with psychological skills development at a younger age was voiced, but this would require a framework to guide the process. Throughout a professional career, player well-being should also be prioritised. This includes assistance both on and off the field, and should continue beyond the player`s transition into retirement. Rugby sevens was included in the 2016 Rio Olympic Games, and interest in the sport has subsequently grown globally. Although the South African sevens team expressed that it was a special experience to win Olympic bronze, the perception was that South Africa does not have an Olympic culture yet and, therefore, there is plenty to learn from other countries in that regard. Using the newly acquired knowledge regarding the demands of rugby sevens, a psychological skills development and well-being programme could be developed and implemented. This should positively contribute to the performance of a rugby sevens team and give them the edge every team strives towards